Wind Tunnel Simulation of the Atmospheric Boundary Layer for Studying the Wind Pattern at Centro de Lançamento de Alcântara - Avelar,Ana Cristina (2012)
Abstract: Centro de Lançamento de Alcântara is the main Brazilian launching center. In spite of presenting several desirable aspects, due to its proximity to the Equator, it has a peculiar topography because of the existence of a coastal cliff, which modifies the characteristics of the atmospheric boundary layer. This may affect rocket-launching operations, especially when associated with safety procedures. This work is a continuation of previous experimental studies about the airflow pattern at this launching center. An improved way of simulating the atmospheric boundary layer in a short-test section wind tunnel using passive methods is presented here. It is also presented a preliminary analysis of the airflow pattern in Centro de Lançamento de Alcântara, at specific positions as the edge of cliff and around the mobile integration tower, from wind tunnel measurements using particle image velocimetry. Three values of Reynolds number, based on the coastal cliff height, l, ranging from 6.8×105 to 2.0×106, were considered.